PENGUASAAN KANJI PADA MAHASISWA TINGKAT III PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Mardiansah Mardiansah; Nana Rahayu; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Kanji is very important to learn in learning Japanese. This is because the Japanese writing system uses kanji. Kanji have a large number and have special characteristics compared to other letters. Therefore kanji is difficult to learn. The purpose of this study was to determine the mastery of kanji in level III students of the Japanese language education study program, Riau University. The research method used is descriptive quantitative method. The results obtained were that from 33 students there were 26 students who answered more than half of the questions correctly. And there were 7 students who answered less than half of the questions correctly.Key Words: Kanji, Ability, Mastering